Urinary microRNAs as a new class of noninvasive biomarkers in oncology, nephrology, and cardiology - Mlčochová, Hana; Héžová, Renata; Meli, Albano C; Slabý, Ondřej (Methods in molecular biology, 2015)
MicroRNAs (miRNAs) are small noncoding RNAs that posttranscriptionally regulate gene expression. In the last decade, number of evidences showing miRNAs contribution to the regulation of apoptosis, cellular proliferation, differentiation, and other important cellular processes is constantly growing. Specific miRNA expression signatures have been identified in variety of human cancers as well as pathologies of cardiovascular and urinary systems. Our chapter focuses on the potential of urinary miRNAs to serve as biomarkers in uro-oncology, nephrology, and cardiology. We discuss in detail recent knowledge about the origin of urinary miRNAs, their stability, quality control, and their utility as a potential new class of biomarkers in medicine. Finally, we summarize the studies focusing on detection and characterization of urinary miRNAs as potential biomarkers in urologic cancers, nephrology, and cardiology.
Keywords: urologické nemoci; nádory; RNA Stability; Female; Urologic Diseases; mikro RNA; stabilita RNA; biologické markery; ženské pohlaví; mužské pohlaví; Humans; lidé; Biomarkers; Male; Neoplasms; nemoci srdce; MicroRNAs; Heart Diseases